Effects of Distinctiveness, Repetition and Semantic Priming on the Recognition of Face Familiarity - BRUCE, VICKI; DENCH, NEAL; BURTON, MIKE (Canadian Journal of Experimental Psychology, 1993)
Three experiments are reported which provide evidence for the independence of effects of repetition from those of distinctiveness and semantic priming in the recognition of familiar faces. In Experiment 1, repetition priming is shown to be additive with face distinctiveness in a face familiarity decision task, where subjects make speeded familiarity decisions to a sequence of famous and unfamiliar faces. Experiment 2 examines the combined effects of distinctiveness and semantic priming. The results suggest that the effect of distinctiveness is additive with that of semantic priming. Experiment 3 uses a more powerful design in which effects of distinctiveness and semantic priming were assessed while all items were repeated three times during the course of the experiment. Effects of repetition and distinctiveness were again additive, as were effects of repetition and semantic priming. Distinctiveness and semantic priming were additive at 1000 ms SOA, though appeared to interact at 250 ms SOA. The results give further evidence for the separation of the mechanisms of semantic from repetition priming, and furthermore suggest that distinctiveness operates at a different locus from those of either of the priming mechanisms.